Use of the PSCHO questionnaire in the patient safety climate assessment: an integrative review (Research, Society and Development, 2021)
Objective: To identify in the literature studies that used the Patient Safety Climate in Healthcare Organizations (PSCHO) questionnaire to assess the patient safety climate in hospital health services. Method: This is an integrative literature review, defined as a concise survey in a specific area. The search and selection of studies were carried out by two reviewers, independently in the databases LILACS, MEDLINE, CINAHL, and WoS. The results were presented using the PRISMA flowchart. Results: Six articles were retrieved in the search, of which four were included and analyzed. The studies were carried out in China and the United States and the dimensions "fear of blame and punishment" and "fear of shame" stood out negatively in Chinese studies. The PSCHO showed similarities when compared to other studies that evaluated the patient's safety climate using other climate questionnaires. Conclusion: The results demonstrated that the PSCHO is useful for assessing the patient's safety climate. The absence of Brazilian studies using the questionnaire indicates a potential for its application in new research, as a strategy for improving the quality and promoting patient safety in Health Organizations.